2011
DOI: 10.1183/09031936.00189710
|View full text |Cite
|
Sign up to set email alerts
|

Short-term safety of thoracoscopic talc pleurodesis for recurrent primary spontaneous pneumothorax: a prospective European multicentre study

Abstract: The safety of talc pleurodesis is under dispute following reports of talc-induced acute respiratory distress syndrome (ARDS) and death. We investigated the safety of large-particle talc for thoracoscopic pleurodesis to prevent recurrence of primary spontaneous pneumothorax (PSP).418 patients with recurrent PSP were enrolled between 2002 and 2008 in nine centres in Europe and South Africa. The main exclusion criteria were infection, heart disease and coagulation disorders. Serious adverse events (ARDS, death or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…MASKELL et al [134] later showed in humans that systemic side-effects differed depending on whether large or small particle talc had been used. A recent Canadian study reported respiratory compromise in 14 out of 138 patients after talc poudrage using only American Food and Drug Administration approved talc [135], whereas two large European prospective cohorts demonstrated the safety of talc used in Europe in terms of incidence of acute respiratory distress syndrome [17,136]. The safety of talc has been further established with the observation that talc poudrage does not alter lung function [117,118,125,137].…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MASKELL et al [134] later showed in humans that systemic side-effects differed depending on whether large or small particle talc had been used. A recent Canadian study reported respiratory compromise in 14 out of 138 patients after talc poudrage using only American Food and Drug Administration approved talc [135], whereas two large European prospective cohorts demonstrated the safety of talc used in Europe in terms of incidence of acute respiratory distress syndrome [17,136]. The safety of talc has been further established with the observation that talc poudrage does not alter lung function [117,118,125,137].…”
Section: Indicationsmentioning
confidence: 99%
“…The last few decades have seen advances in both the diagnosis and the treatment of spontaneous pneumothorax. Some newer approaches, however, remain poorly implemented in standard clinical practice [4,6,[10][11][12][13][14][15][16][17]. The European Respiratory Society (ERS) is updating this statement regarding PSP in order to present the latest developments and concepts, with the aim of improving clinical management and stimulating further high quality research in this important area.…”
Section: Introductionmentioning
confidence: 99%
“…Its safety profile and efficacy in clinical practice is well documented nowadays [1,2]. It induces an inflammatory reaction which promotes pleural symphysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The reported in the past sporadic cases of pneumonitis and ARDS after talc poudrage of the pleural cavity were not observed in the relatively recent large multicentre European study of 418 patients who underwent thoracoscopic talc pleurodesis for the prevention of PSP recurrence (16). Talc is definitely considered to be a safe agent to perform pleurodesis, even in benign pleural diseases such as PSP (16,17).…”
Section: Read With Great Interest the Innovative Technical Article mentioning
confidence: 98%
“…Surgical access via uniportal or periareolar VATS procedures does not allow extensive pleurectomy, while efficient talc poudrage can be applied by any of the existing accesses. Talc poudrage of the pleural cavity is also connected with specific complications, such as talcoma formation (15,16). The reported in the past sporadic cases of pneumonitis and ARDS after talc poudrage of the pleural cavity were not observed in the relatively recent large multicentre European study of 418 patients who underwent thoracoscopic talc pleurodesis for the prevention of PSP recurrence (16).…”
Section: Read With Great Interest the Innovative Technical Article mentioning
confidence: 99%